Testing the keepin’ it REAL Substance Use Prevention Curriculum among Early Adolescents in Guatemala City. - Kulis, Stephen S. (Prev Sci, 2019)
This article describes a test in Guatemala City of Mantente REAL, a linguistically adapted version of the keepin’ it REAL universal substance use prevention curriculum for early adolescents that teaches culturally grounded drug resistance, risk assessment and decision making skills. Academic researchers collaborated with a local non-profit to recruit and randomize 12 elementary schools in Guatemala City to intervention and comparison conditions. Regular classroom teachers were trained to deliver the ten-lesson Mantente REAL (MR) manualized curriculum to sixth grade students. Parents provided passive consent and students gave active assent for data collection, which occurred between February 2013 and September 2014. Two academic year cohorts of students participated (n=676; 53% male; M age=12.2). All students completed a pretest questionnaire before the curriculum lessons began in intervention schools and a posttest (87% matched) four months later, one month after the final lesson. We assessed the MR intervention with paired t tests, effect sizes (Cohen’s d), and general linear models adjusted for baseline, attrition, non-linear distributions, and school-level clustering. Results indicated that MR can be an effective school-based prevention approach in Guatemala. The MR participants reported pretest-to-posttest changes in desirable directions on substance use behaviors, attitudinal antecedents of substance use, and acquisition of drug resistance skills. The comparison group generally changed in undesirable directions. In linear models the MR participants, relative to the comparison group, reported less cigarette and marijuana use, less positive drug use expectancies, and greater use of drug resistance skills. Intervention effect sizes were between .2 and .3.